Impact of ion-pairs for the determination of multiclass antimicrobials residues in honey by LC-MS/MS. Issue 12 (2nd December 2017) - EL Hawari, Khaled; Daher, Zeina; Verdon, Eric; AL Iskandarani, Mohamad
ABSTRACT: This study examines the behaviour of volatile perfluorinated carboxylic acids used as ion-pairing reagents for the separation of multiclass antimicrobial residues in honey (tetracyclines, sulphonamides, macrolides, and aminoglycosides). Heptafluorobutanoic acid and pentafluoropentanoic acid were compared as mobile phase additives at concentrations of 0–20 mmol.L −1 using reversed-phase chromatography. Our objective was to find optimal conditions that enable the separation of antimicrobials with a minimum loss in sensitivity and efficiency. The influence of ion pairing on chromatographic performance was examined. Results showed that heptafluorobutanoic acid was able to separate aminoglycosides faster and more efficiently than pentafluoropentanoic acid, but at low concentrations of heptafluorobutanoic acid between 2.5 and 5 mM, tetracyclines showed poor chromatographic efficiency. A concentration of 10 mM was found to be optimal for all studied veterinary drugs. The method was then applied to determine multiclass antimicrobial residues in honey. Based on validation data, the mean recoveries of analytes ranged between 93% and 104%, and the intermediate precisions were <21%. The decision limit (CCα) and detection capability (CCβ) were in the ranges of 5–25 and 7–33 μg kg –1, respectively. The method was found to be suitable for use in analysis of veterinary drugs with a broader group of compounds found in food-producing animals. Graphical Abstract: